De l'expression du point de vue à l'anticipation textuelle : le rôle de à première vue - Véronique Lenepveu (Discours)
We propose a semantic and pragmatic analysis of the french locution à première vue (lit. “at first sight”) when it indicates a point of view (in the sense of Nølke, 1994) and plays a role in textual structuration (Charolles, 1997). In this perspective, we study discursive patterns in which à première vue is employed in contrast with expressions which signal an evolution of the judgment of the speaker (à mieux regarder, à y regarder de plus près, à bien y réfléchir, en y réfléchissant, tout compte fait, tout bien considéré…). All these expressions can appear in peripheric positions. They express a de dicto aspectual value, by selecting a phase of an enonciative process which consists in taking in consideration a situation in order to formulate a more or less settled judgment.